Understanding the Trends and Management System in Colonial Prisons: A Literary Survey - Bohier, Jalal (Pakistan Languages and Humanities Review, 2023)
In order to better understand how European powers used prisons as instruments of social control, political repression, and economic exploitation, this review examines the practices and administrative frameworks found in colonial jails. In addition to punishing offenders, colonial prisons also served to stifle opposition and uphold colonial hierarchies. These institutions were frequently based on European models but were modified to fit local circumstances. Racist segregation, the exploitation of forced labor, and the eradication of indigenous cultures are important tendencies. Inadequate health care, severe discipline, and little focus on rehabilitation were the hallmarks of management regimes. Prisons were built to be places of control, but they also developed into hubs of political awareness and resistance, especially among political inmates. The methodological approach of this research study is comparative qualitative techniques. The results of this article show that the prison literature has been produced in abundance, most of which has criticized the main institutional issues in colonial prisons.